1997
DOI: 10.1007/bf01834062
|View full text |Cite
|
Sign up to set email alerts
|

European Spine Society —The AcroMed prize for spinal research 1997

Abstract: A study was conducted to find out whether in a rear-impact motor vehicle accident, velocity changes in the impact vehicle of between 10 and 15 km/h can cause socalled "whiplash injuries". An assessment of the actual injury mechanism of such whiplash injuries and comparison of vehicle rear-end collisions with amusement park bumper car collisions was also carried out. The study was based on experimental biochemical, kinematic, and clinical analysis with volunteers. In Europe between DM 10 and 20 billion each yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Of the remaining 34 studies, one was excluded as the authors reported barrier equivalent velocity (BEV) rather than delta V [ 18 ]. Among the 33 remaining studies there were data from 408 individual crash tests that could be abstracted for description and analysis [ 16 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. The number of unique test subjects could not be determined from the studies, as multiple studies were performed by the same authors who also included themselves as test subjects, and most papers described two or more crash tests per subject (making the likely number of unique subjects in the included studies between 100 and 200).…”
Section: Resultsmentioning
confidence: 99%
“…Of the remaining 34 studies, one was excluded as the authors reported barrier equivalent velocity (BEV) rather than delta V [ 18 ]. Among the 33 remaining studies there were data from 408 individual crash tests that could be abstracted for description and analysis [ 16 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. The number of unique test subjects could not be determined from the studies, as multiple studies were performed by the same authors who also included themselves as test subjects, and most papers described two or more crash tests per subject (making the likely number of unique subjects in the included studies between 100 and 200).…”
Section: Resultsmentioning
confidence: 99%
“…A complete collection of the available volunteer literature resulted in a dataset of 1984 total volunteer exposures from 51 individual studies. 5 10 , 12 , 15 18 , 22 26 , 28 – 32 , 34 41 , 43 , 46 – 54 , 56 59 , 61 – 64 , 66 – 68 , 73 On average, each study performed 40 tests with a range from 1 to 484 tests and used 51 subjects with a range of 1 to 65 volunteers per study. Many of the volunteers experienced more than one exposure (Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Unique to this investigation, identified patients with severe neck symptoms and concussions had a higher incidence of reported motion sickness history and scored higher on concussion indices (CP screen, VOMS, and ImPACT). The concussion indices data may implicate a higher-energy mechanism of injury as is seen in WAD 31. Meanwhile, the association of motion sickness history with severe neck system may implicate a disturbance to the vestibular system that may be best addressed with case-specific interventions including cervicovestibular rehabilitation to promote recovery 7…”
Section: Discussionmentioning
confidence: 99%